Благодійність населення східноєвропейських країн із радянським минулим - Сальнікова, Світлана Анатоліївна; Salnikova, Svitlana A. (Східноєвропейський національний університет імені Лесі Українк, 2014)
За допомогою аналізу досягнень низки країн щодо ставлення їхнього населення до благодійної допомоги із застосуванням методики побудови Світового індексу благодійності, обґрунтовано неспроможність порівняння рейтингових місць країн через (1) різну кількість країн-учасниць у кожній хвилі та (2) відсутність критеріїв належності країни до певного рангу з урахуванням помилки вимірювання. Більш відповідним для порівняння є Індекс благодійності (%), згідно з яким країни «Східної Європи, пострадянські», особливо без Росії, демонструють не гірші показники, ніж східні держави Євросоюзу («Східна Європа, посткомуністичні, ЄС»), і значно кращі, ніж північні («Північна Європа, пострадянські, ЄС»).

Analysis of the achievements of some countries in attitudes their population to the charitable help implemented by applying techniques of construction of World Giving Index in this study. Author proves the inability of comparison of ranking through (1) different number of countries-participating in each wave and (2) lack of criteria of definition of belonging of the country to certain rank considering measurement error. Therefore such an indicator as the averaged Giving Index (%) is more relevant for comparison. In particular, among European post-Soviet countries according to data for the last five years (2010–2014) Belarus and Moldova demonstrate of the best results, Russia – the worst; Ukraine – the most dynamic. These countries as a region «Eastern Europe, post-Soviet», especially without Russia, show no worse an aggregate indicator of Giving Index than the eastern EU countries (region «Eastern Europe, post-communist, EU»), and much better than the northern EU countries (region «North Europe, post-Soviet, EU» – Estonia, Latvia, Lithuania).
The Charity of Population of East European Countries with the Soviet Past
Keywords: Світовий індекс благодійності; порівняльний аналіз; обґрунтування; рейтинг; громадянське суспільство; World Giving Index; comparative analysis; validity; ranking; civil society